2018
DOI: 10.1080/2162402x.2018.1532762
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of post-transcriptional regulation for IFN-γ in tumor-infiltrating T cells

Abstract: Protective T cell responses against tumors require the production of Interferon gamma (IFN-γ). However, tumor-infiltrating T cells (TILs) gradually lose their capacity to produce IFN-γ and therefore fail to clear malignant cells. Dissecting the underlying mechanisms that block cytokine production is thus key for improving T cell products. Here we show that although TILs express substantial levels of Ifng mRNA, post-transcriptional mechanisms impede the production of IFN-γ protein due to loss of mRNA stability.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 49 publications
5
51
1
Order By: Relevance
“…Whereas the percentage of early activated CD69+ T-GREAT cells in response to ME49 and MAS infections was slightly decreased to Nlrp3-/- compared to WT BMDMs ( Fig 9A ), IFNγ transcript levels in the activated CD69+ population dropped by 50–70% ( Fig 9B ), suggesting NLPR3 induces a macrophage-derived signal required for IFNγ transcription in activated CD8 T cells. Co-stimulation determines transcriptional regulation of IFNγ in tumor-infiltrating T cells [ 118 ], and in its absence, enforces post-transcriptional silencing of IFNγ in anergic self-reactive T cells [ 119 ], perhaps underscoring the blunted transcriptional ( Fig 9B ) and translational CD8 T cell IFNγ response to parasite-infected Nlrp3 -/- BMDMs ( Fig 8 ). To determine whether NLRP3 regulates co-stimulatory pathways, a variety of co-stimulatory ligands and the PD-L1 inhibitory receptor were measured on infected BMDMs.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the percentage of early activated CD69+ T-GREAT cells in response to ME49 and MAS infections was slightly decreased to Nlrp3-/- compared to WT BMDMs ( Fig 9A ), IFNγ transcript levels in the activated CD69+ population dropped by 50–70% ( Fig 9B ), suggesting NLPR3 induces a macrophage-derived signal required for IFNγ transcription in activated CD8 T cells. Co-stimulation determines transcriptional regulation of IFNγ in tumor-infiltrating T cells [ 118 ], and in its absence, enforces post-transcriptional silencing of IFNγ in anergic self-reactive T cells [ 119 ], perhaps underscoring the blunted transcriptional ( Fig 9B ) and translational CD8 T cell IFNγ response to parasite-infected Nlrp3 -/- BMDMs ( Fig 8 ). To determine whether NLRP3 regulates co-stimulatory pathways, a variety of co-stimulatory ligands and the PD-L1 inhibitory receptor were measured on infected BMDMs.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their well-known effect in boosting innate immune responses and enhancing Ag presentation, we reveal that TLR ligands can also directly augment T cell responses. We recently showed that tumor-infiltrating T cells lose their capacity to produce cytokines because they fail to stabilize the cytokine mRNA (70). It is therefore tempting to speculate that TLR2 could promote antitumoral T cell responses by providing costimulatory signals to T cells and prolonging cytokine mRNA t 1/2 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their well-known effect in boosting innate immune responses and enhancing antigen presentation, we reveal that TLR ligands can also directly augment T cell responses. We recently showed that tumor-infiltrating T cells lose their capacity to produce cytokines because they fail to stabilize the cytokine mRNA (70). It is therefore tempting to speculate that TLR2 could promote anti-tumoral T cell responses by providing costimulatory signals to T cells and prolonging cytokine mRNA half-life.…”
Section: Discussionmentioning
confidence: 99%